The Role of Crk Adaptor Proteins in T-Cell Adhesion and Migration - Braiman, Alex; Isakov, Noah (Frontiers in Immunology, 2015)
Crk adaptor proteins are key players in signal transduction from a variety of cell surface receptors. They are involved in early steps of lymphocyte activation through their SH2-mediated transient interaction with signal transducing effector molecules, such as Cbl, ZAP-70, CasL, and STAT5. In addition, they constitutively associate, via their SH3 domain, with effector molecules, such as C3G, that mediate cell adhesion and regulate lymphocyte extravasation and recruitment to sites of inflammation. Recent studies demonstrated that the conformation and function of CrkII is subjected to a regulation by immunophilins, which also affect CrkII-dependent T-cell adhesion to fibronectin and migration toward chemokines. This article addresses mechanisms that regulate CrkII conformation and function, in general, and emphasizes the role of Crk proteins in receptor-coupled signaling pathways that control T-lymphocyte adhesion and migration to inflammatory sites.